NANOFLUIDS WITH RECENT APPLICATION & FUTURE TRENDS - Yukta Sawant; Kunal Pathare; Rakesh Patel; Prof. Prathamesh Choughule (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper provides an overview of enhanced properties of nanofluids which are used in plethora of engineering applications ranging from use in automotive industry to medical arena to use in power plant cooling systems. In addition , it also highlights future work and possibilities. The novel concept of nanofluids in the spring of 1993, talented and studious thermal scientists and engineers in the rapidly growing nanofluids community have made scientific breakthrough not only in discovering unexpected thermal properties of nanofluids , but also in proposing new mechanisms behind enhanced thermal properties of nanofluids. As a result , this research topic of nanofluids has been receiving increasing attention worldwide.